Factores de riesgo cardiovascular y calidad de vida en adolescentes de la Unidad Educativa Fiscomisional Daniel Álvarez Burneo - Carrión Ruiz, Brayan Paúl (2020)
The cardiovascular risk factors predispose adolescents to suffer cardiovascular diseases in the future. The purpose of this study was to identify modifiable and non-modifiable cardiovascular risk factors; establish the quality of life; and establish the relationship of cardiovascular risk factors and quality of life in adolescents who are enrolled in the third year of baccalaureate of the Unidad Educativa Fiscomisional "Daniel Álvarez Burneo" of Loja, in 2018. It was a study of quantitative approach and cross section; developed in a population of 228 adolescents. Obtaining as results: the female sex from 17 to 18 years prevailed in the studied population, being the inappropriate feeding (74.12%), the inadequate physical activity (32.02%), sedentarism (36.4%) and elevated BMI (25.05%), the most prevalent modifiable cardiovascular risk factors; the history of hypertension (53.5%) and DM (54.82%) were found in more than half of the adolescents, constituting the most frequent non-modifiable cardiovascular risk factors. About one third of adolescents have regular (25.88%) or deficient (5.7%) quality of life, being able to confirm that the lack of this quality of life predisposes adolescents to present higher cardiovascular risk factors, fundamentally those of modifiable nature, likewise, the absence of a healthy lifestyle predisposes adolescents to have a poor quality of life. Keywords: cardiovascular disease, inappropriate feeding, Hypertension, Diabetes.